On the precipitation susceptibility of monsoon clouds to aerosols using high-altitude ground-based observations over Western Ghats, India. (July 2018) - Leena, P.P.; Anilkumar, V.; Sravanthi, N.; Patil, R.; Chakravarty, K.; Saha, S.K.; Pandithurai, G.
Abstract: Precipitation susceptibility of monsoon clouds to changes in aerosols has been studied initially by utilizing ground based observations from a High Altitude Cloud Physics Laboratory (HACPL), Mahabaleshwar, India collected during monsoon seasons and later compared with the results obtained from satellite observations. Cloud condensation nuclei (CCN) concentration, rain intensity and integrated liquid have been taken from ground based observations for calculating precipitation susceptibility. As a first step, we have analyzed the temporal variation of CCN concentration, rain intensity and integrated liquid water during monsoon season. It is observed that all three parameters exhibit strong diurnal variation with two peaks i.e. in morning and afternoon. CCN showed strong morning peak whereas other two showed during afternoon hours. Later precipitation susceptibility has been estimated using CCN as aerosol proxy and it is higher ∼0.65 for the integrated liquid water ranging from 0.6 to 0.8 mm. Secondly, we have compared ground based observation with satellite observations carried out using aerosol optical depth (AOD), rain rate and liquid water path. Satellite observations showed that precipitation susceptibility, S0, using AOD as aerosol proxy is higher (S0  = 0.98) for liquid water path ranging from 800 to 1000 gm -2 . It is also seen that the results are in agreement with the earlier reported results especially with the report from tropical region. Present analysis also showed that the precipitation is getting suppressed at medium range of integrated liquid/liquid water path. This is the first such study from Indian region explicitly using ground-based observations. Highlights: Precipitation susceptibility (S0 ) is investigated using ground based observations. S0 found to be maximum (∼0.65) for the integrated liquid ranging from 0.6 to 0.8 mm. Satellite data shows higher S0 (∼0.98) for LWP ranging from 800 to 1000 gm -2 . Susceptibility is higher for medium LWP in agreement with previous reports.